Analisis Kinerja Keuangan, Ukuran Perusahaan, Leverage, dan Volume Penjualan terhadap Corporate Social Responsibility - Raudhah Almas Barlinti; Muhammad Abdul Aris (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This observation aims to analyze financial performance, company size, leverage, and sales volume on Corporate Social Responsibility (CSR) in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Research methodology: This observation is a quantitative research which uses secondary data in the form of annual reports. This observation uses 207 samples of manufacturing companies during 2018-2020. This study uses multiple linear regression analysis techniques, classical assumption test, and partial hypothesis testing using SPSS v.26 application program. Results: The result of this observation is that financial performance and company size are factors that affect Corporate Social Responsibility (CSR), while leverage and sales volume are not factors that affect Corporate Social Responsibility (CSR). Limitations: The limitations of this study are only focused on the manufacturing sector, companies that disclose financial statements in rupiah, and period limitations. Contribution: These observations can be used to determine the factors that influence Corporate Social Responsibility (CSR) and are expected to provide information for investors.